UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA MELALUI MIND MAP DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA MATA KULIAH ANATOMI FISIOLOGI MANUSIA - Gustina Indriati; Evrialiani Rosba; Ria Kasmeri (Ta'dib, 2015)
Based on learning activities observation in human anatomy and fisiology major is low, like pay attention to the lecture, questioning, most of students talking each other, when they did the task the students more choose made in group. Activities learning of student is low because the students didn’t have motivation in learning process, although the lecture has discution metode in learning process. The purpose of this research are to improve activities and student result of the learning. This research had used cooperative learning model with the type is STAD trough mind map in human anatomy and fisiology major.  This research have been done to the students in STKIP. This research are action research that did in two phase. The phase are: Planning, doing, observation, and reflection. The data obtained through observation sheet documentation and test. Data that analysis from activities students and learning result of the students. The result of this research showed the improved of activities and learning result of the students. based on activities learning of student that get from cycluse 1 to the cycluse 2, showed that the increase of activities of the students like pre test( 98%) and post test (100%) with very good category in cycluse 1. In cycluse 2 become 5 activities like pre test (98%), looking to the lecture (93%), active to followed the discution (88%), making mind map (90%), followed post test (100%) with very good category. Result of learning in cycluse 1 just 52%, in cycluse 2 increased and become 83%. Based on the result that been concluded using cooperative learning model type of STAD through mind map in  human anatomy and fisiology major can increase activities and result learning of the students.Kata kunci: Kooperatif STAD, Mind Map, Aktivitas, Hasil Belajar, Siklus